Creep Strain and Permeability Evolution in Cracked Granite Subjected to Triaxial Stress and Reactive Flow. (10th December 2018) - Zhang, Fan; Zhao, Jianjian; Hu, Dawei; Sheng, Qian; Shao, Jianfu
Abstract : Fluid flow and fluid-rock interaction mainly take place in fracture network, consequently resulting in deformation and permeability variation of rock and deterioration of the wellbore performance. Mechanical-reactive flow coupling creep tests are performed on cracked granite under various confining pressures and acid and alkaline solution flows. The testing results show that the confining pressure and solution pH significantly influence the creep deformation, creep strain rate, and permeability. A primary creep stage and secondary creep stage are observed in all creep tests in this study; notably, the sample under a confining pressure of 10 MPa and acid solution injection undergoes creep failure for over 2700 hours. The acid solution has a more obvious influence on the creep behavior than that of the alkaline solution. With an increase in confining pressure, the total creep strain and creep strain rate in the samples gradually decrease during the injection of either solution. The permeability of the samples injected with either solution gradually deceases during the testing process, and this deceasing rate increases with the confining pressure. The scanning electron microscopy observations on the crack surfaces after the creep tests show that the surfaces of the fractures injected with the acid solution are smooth due to the dissolution of the matrix, while those injected with the alkaline solution include voids due to the dissolution of quartz. These experimental results could improve the understanding of the long-term transport and mechanical behaviors of wellbore.